(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
In the Sixties, many times the cinematographic representation focused on male grotesque masks, which contributed to the representation of the malaise of a society populated by weak individuals. This article proposes the analysis of a tragic female mask, the one embodied by Sandra Milo, whose grotesque image, in the films interpreted in the early Sixties, is an irreverent testimony of an upside down world in which sexual hierarchies are overturned and social rules are contradicted. At the same time, through the eroticization of her actress body, primordial desires and sexual instincts emerge in stark contrast to social conventions and public morals, but they are, however, quite far from any form of emancipation.